Hubungan antara Narrative Engagement dengan Binge Watching pada Penonton K-drama - Riska Miranti; Suci Nugraha (UNISBA Press, 2023)
Abstract. The development of television into internet-based online video streaming has given viewers control over their own pace of media consumption and option to watch several episodes in one sitting. This refers to the phenomenon of binge watching. The phenomenon of binge watching through this online streaming platform has also developed among Korean drama (K-drama) viewers. This phenomenon has negative consequences both physically and mentally, moreover, it can also develop into addiction behaviour. Nevertheless, research on antecedents or factors that affect binge watching is still lacking, especially in Indonesia. One of the factors that become the antecedent of binge watching is involvement factor in narrative or known as narrative engagement. This study aims to determine the relationship between narrative engagement and binge watching behavior among K-drama viewers. This study used the correlation method with Spearman’s rho data analysis. The measuring instruments used in this study is the Narrative Engagement Scale by Buselle and Bilandzic (2009) and The Single-Program Binge Watching (SPBW) by Viens and Farar (2021) and adapted into the Indonesian context by researcher. The final sample in this study were 302 respondents aged 18-25 years, living in Jakarta and watched more than one episodes of K-drama at one sitting. The results showed a significant level of 0.000 < 0.05, with a correlation (r) 0.412. There is a significant positive relationship between narrative engagement and binge watching among K-drama viewers. Abstrak Perkembangan pada tayangan televisi menjadi video online streaming berbasis internet membuat penonton memiliki kendali atas laju konsumsi media mereka sendiri dan kebebasan untuk menonton beberapa episode sekaligus dalam satu waktu, yang menimbulkan fenomena binge watching. Fenomena binge watching melalui layanan platform online streaming ini juga berkembang pada penonton Korean drama (K-drama). Fenomena ini menimbulkan konsekuensi negatif baik dari segi fisik maupun mental, serta bisa berkembang menjadi adiksi. Meskipun demikian, penelitian mengenai anteseden atau faktor yang mempengaruhi binge watching masih sangat terbatas, terutama di Indonesia. Salah satu faktor yang menjadi antiseden perilaku binge watching muncul dari faktor keterlibatan terhadap narasi atau narrative engagement. Penelitian ini bertujuan untuk mengetahui hubungan antara narrative engagement dengan perilaku binge watching pada penonton K-drama. Penelitian ini menggunakan metode korelasi dengan analisis data Rank Spearman. Alat ukur yang digunakan dalam penelitian ini Narrative Engagement Scale oleh Buselle dan Bilandzic (2009) dan Single-Program Binge Watching (SPBW) oleh Viens dan Farar (2021) yang telah diadaptasikan ke dalam bahasa Indonesia oleh peneliti. Sampel akhir dalam penelitian ini berjumlah sebanyak 302 responden berusia 18-25 tahun yang tinggal di Jakarta yang sedang menonton K-drama dengan cara menonton lebih dari satu episode sekaligus dalam satu waktu. Hasil penelitian menunjukkan tingkat signifikansi sebesar 0.000 < 0.05, dengan korelasi (r) sebesar 0.412 sehingga diketahui terdapat hubungan positif yang signifikan antara narrative engagement dengan binge watching pada penonton K-drama.